Attachment security and intergroup contact. Issue 11 (4th June 2015) - Boccato, Giulio; Capozza, Dora; Trifiletti, Elena; Di Bernardo, Gian Antonio
Abstract: The contact hypothesis suggests that the interaction between members of different groups decreases prejudice. Moderators and mediators shaping this link have been investigated. However, research about the factors that facilitate contact is not frequent. This article examines secure attachment as an antecedent of contact. Three studies provide information about various aspects of the relationship between secure attachment and contact: security is positively associated with (a) intergroup contact, which in turn is related to reduced prejudice (Study 1); (b) implicit approach tendencies toward the outgroup (Study 2); and, once again, (c) with contact through the indirect effect of openness to exploration (Study 3). In the discussion, we recommend priming both secure and insecure schemas to investigate their unique effects on intergroup contact.